Operator Competence and Management of the Village Financial System: A Study on the Use of Siskeudes in Sumenep District - Rasaili, Wilda (Neo Journal of economy and social humanities, 2022)
Abstract. Technology-based village financial system management in Sumenep Regency has been implemented since 2018. The management is in the form of the Siskeudes application which helps accelerate planning, data collection and village financial management, and encourages transparency of the village management system. The main obstacle to using the Siskeudes application is the capacity and competence of village officials and village operators. This research uses a qualitative method with a case study approach and obtains data through in-depth interviews, documentation and observations. The results of the study suggest that the siskeudes application is very helpful in managing village finances, and the use of the siskeudes application must be supported by the competence of village officials and operators by covering, 1) educational qualifications, 2) the intensity of financial management training with and using the siskeudes application, and 3) self-development efforts. village officials and operators. Competence or resources of village officials and village operators as the main factor in the smooth management of technology-based village financial systems. Technology-based financial system management supported by operator competence can accelerate reporting, ease public accessibility and financial management innovation. Keywords: Competence, village operator, financial system management, siskeudes application.